Assessment of Sex, Age, and Metabolism Relationships to Serum Thyroid Concentrations in Retired Alaskan Husky Sled Dogs - Lenfest, Margret; Loftus, John P.; Huson, Heather J.; Gudkov, Andrei; Andrianova, Katerina; Fleyshman, Daria; Wakshlag, Joseph (Frontiers in Veterinary Science, 2022)
Sled dogs are purpose-bred dogs selected for endurance work. Prior studies in racing dogs showed that serum thyroid parameters (total T4, free T4, and T3) are lower than the reference range in approximately 25% of dogs. Whether this is related to training, breeding, or body condition remains unclear. We hypothesized that retired sled dogs of normal body condition (9–13 years old) would have predominantly normal serum thyroid parameters and that serum thyroid status would be correlated to energy consumption based on metabolic body weight. Eighty-six sled dogs who were deemed healthy on physical exam, not on confounding medications, and without a prior diagnosis of hypothyroidism were included. All dogs' mean body condition scores were 5.1 ± 0.4 and body weight 24.5 ± 4.2 kg at fasting blood collection with stable dietary intake for 3 months before sampling. The total T4, free T4, and T3 serum concentrations were 23.4 ± 9.1 nmol/L, 9.53 ± 4.3 pmol/L, and 0.93 ± 0.39 nmol/L, respectively, with 38% lower than the reference range for total T4, 45% for free T4, and 37% for T3. All dogs were negative for thyroglobulin antibody, and TSH results were within normal ranges. Pearson's correlates based on kilocalories consumed on a metabolic body weight basis for total T4 (R = 0.14), free T4 (R = 0.01) and T3 (R = 0.23) showed poor correlation. No differences were observed between thyroid hormones and age, breed, or sex. Inactive, retired sled dogs can be misdiagnosed with hypothyroidism; therefore, our data suggests that misdiagnosis of hypothyroidism can occur and that the racing Alaskan sled dog has a unique reference range that should be considered when assessing serum thyroid status.